2013
DOI: 10.1038/ki.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

The erythropoietin receptor is a downstream effector of Klotho-induced cytoprotection

Abstract: Although the role of the erythropoietin (Epo) receptor (EpoR) in erythropoiesis has been known for decades, its role in non-hematopoietic tissues is still not well defined. Klotho has been shown and Epo has been suggested to protect against acute ischemia-reperfusion injury in the kidney. Here we found in rat kidney and in a rat renal tubular epithelial cell line (NRK cells) EpoR transcript and antigen, and EpoR activity signified as Epo-induced phosphorylation of Jak2, ErK, Akt, and Stat5 indicating the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 93 publications
2
61
0
2
Order By: Relevance
“…We mimicked IRI with H 2 O 2 and found that H 2 O 2 -induced lactate dehydrogenase (LDH) release was reduced by coincubation with aKlotho ( Figure 8A) as previously reported. 16 The new finding, however, was that aKlotho increased the LC3-IIto-LC3-I ratios and decreased p62 protein in OK cells ( Figure 8B) and increased the number of GPF-LC3 punctae (autophagosomes) in OK cells transfected with GFP-LC3 ( Figure 8, C and D), thereby confirming the in vivo findings of higher baseline autophagic flux in the kidney of Tg-Kl mice compared with WT mice ( Figure 7B). Bafilomycin A1 (Baf), an inhibitor of lysosomal acidification and also, an autophagy inhibitor, 68 increased the ratios of LC3-II to LC3-I and p62 ( Figure 8B), increased GPF-LC3 punctae ( Figure 8, C and D), and also, blunted aKlotho-induced elevation of autophagic flux ( Figure 8, B and C).…”
Section: Murine Model Of Post-aki Ckdsupporting
confidence: 77%
See 2 more Smart Citations
“…We mimicked IRI with H 2 O 2 and found that H 2 O 2 -induced lactate dehydrogenase (LDH) release was reduced by coincubation with aKlotho ( Figure 8A) as previously reported. 16 The new finding, however, was that aKlotho increased the LC3-IIto-LC3-I ratios and decreased p62 protein in OK cells ( Figure 8B) and increased the number of GPF-LC3 punctae (autophagosomes) in OK cells transfected with GFP-LC3 ( Figure 8, C and D), thereby confirming the in vivo findings of higher baseline autophagic flux in the kidney of Tg-Kl mice compared with WT mice ( Figure 7B). Bafilomycin A1 (Baf), an inhibitor of lysosomal acidification and also, an autophagy inhibitor, 68 increased the ratios of LC3-II to LC3-I and p62 ( Figure 8B), increased GPF-LC3 punctae ( Figure 8, C and D), and also, blunted aKlotho-induced elevation of autophagic flux ( Figure 8, B and C).…”
Section: Murine Model Of Post-aki Ckdsupporting
confidence: 77%
“…OK cells were treated with H 2 O 2 and/or autophagy modulators (inducers or suppressors) in the presence or absence of aKlotho protein. Cell lysates were prepared 16,17 and immunoblotted for LC3 protein. Supernatants from cell culture media were used for measurement of LDH release as we described previously.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…α-Klotho and EPO can be regulated by each other [38,39]. Obviously, the role of α-klotho is very similar to the TCM theory of "kidneys essence generating marrow and producing blood."…”
Section: Renal Endocrine and The "Kidney Stores Essence" Theorymentioning
confidence: 68%
“…Early studies on EPO-R showed that this receptor is only expressed in cells of the erythroid lineage, emphasizing that the action of EPO is limited to red blood cell manufacturing, while further studies divulged the wide expression of the EPO-R, increasing the likelihood of extra-hematopoietic effect of EPO (Wang et al, 2014). The detection of EPO-R mRNA in the brain, heart, retinal, skeletal, muscle, and kidney cells makes it a promising target to study its untold functions (Morishita et al, 1997;Wu et al, 1999;Noguchi et al, 2008;Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%